Climbing the ladder: an evaluation of three different anguillid eel climbing substrata and placement of upstream passage solutions at migration barriers. (20th February 2019) - Watz, J.; Nilsson, P. A.; Degerman, E.; Tamario, C.; Calles, O.
Abstract: Conservation programmes for endangered, long‐lived and migratory species often have to target multiple life stages. The bottlenecks associated with the survival of juvenile anguillid eels migrating into inland waters, the survival and growth of the freshwater life stage, as well as the recruitment and survival of silver eels, migrating back to the ocean to spawn, must be resolved. In this study, we focus on the efficiency of passage solutions for upstream‐migrating juveniles. Such solutions can consist of inclined ramps lined with wetted climbing substrata. We evaluated different commonly used substrata in a controlled experiment, recorded eel behaviour at the entrance of the ramp with infrared videography and validated the experimental results at a hydropower dam, where we also investigated the effects of ramp placement on performance. In the experiment on eel substratum selection, 40% of the eels passed in lanes with studded substratum, whereas only 21 and 5% passed using open weave and bristle substrata respectively. Video analysis revealed that the studded substratum attracted more approaches and initiated climbs than the other substrata, but once a climb had been initiated, passage success rates did not differ between substrata. Eels using the studded substratum climbed 26% faster than those using the bristle substratum and almost four times as fast as those climbing in the open weave. The superior performance of the studded substratum was supported by data from the field validation. Moreover, ramps positioned by the bank with low water velocities caught the most eels, but proximity to the dam had no effect on performance. To strengthen the European eel population, more juveniles need to reach their freshwater feeding grounds. A critical step to achieve this increase is to equip upstream passage solutions with suitable substrata and to optimize ramp placement at migration obstacles. Abstract : To strengthen the European eel population, more juveniles need to reach their freshwater feeding grounds, and a critical step to achieve this increase is to equip upstream passage solutions with suitable substrata and to optimize ramp placement at migration obstacles. We evaluated different commonly used substrata in a controlled experiment, recorded eel behaviour at the entrance of the ramp with infrared videography and validated the experimental results at a hydropower dam, where we also investigated the effects of ramp placement on performance. Eels were more attracted to, initiated more climbs and climbed faster in the studded substratum than in the open weave and bristle substrata, results that were supported by the field validation. Moreover, ramps positioned by the bank with low water velocities caught the most eels, but proximity to the dam had no effect on performance.